Quand la gestion intégrée redessine les contours d’une aire protégée : le cas du parc marin en mer d’Iroise - Véronique Van Tilbeurgh (Éditions en environnement VertigO, 2006)
The aim of the article is to show the transformation of a project of marine protected area by the introduction of the notion of integrated Coastal Zone Management. This transformation is analyzed through the environmental objectives of the project and recombinations between the participants in negotiations about its creation. We show that the integrated management, while defining mainly a procedure, provides a flexible framework allowing an interplay of alliances between actors. The flexibility of the frame of reference rests on the mobilization of specific conceptual tools entering the definition of integrated management and modifying the designs of space and time as well as the forms of regulation of the uses. This article is based on a research, undertaken between 1998 and 2006 in Brittany, where the creation of a marine park is discussed.